Modelos para estimativa da radiação de onda longa atmosférica no Cerrado mato-grossense - Carrilho Sobrinho, Flair José (2011)
This study aimed to evaluate and parameterize models to estimating the atmospheric long wave radiation (Ld) in the Cerrado Mato-grossense, considering the sky coverage in terms of clear-sky, partly cloudy and overcast. Taking into account that measurements of Ld are rare, and that this parameter is usually obtained indirectly through various models available in the literature we decided in this study, analyze 107 models for the estimation of Ld. The data used in this study were obtained of equipment installed in a micrometeorological tower 19 meters at Miranda farm in Santo Antônio de Leverger - MT, between the months of june and july, and october and november 2009 totalizing 5856 measures. Estimates of Ld obtained from these formulations, the best performing ones were the ones with the smallest statistical errors and the highest index and coefficients as of determination (R 2 ), the Pearson correlation (r), the Wilmott index of “agreement” (1982) (d) and the Camargo & Sentelhas index of “performance” (1997) (c). It can be observed that for conditions clear skies, partly cloudy and overcast, the models to estimate the long-wave irradiance, in its original formulation, which showed the best statistical indices and, therefore, those best adapted for the “Cerrado Mato-grossense” (Brazilian savanna in the Mato Grosso state), in the period studied were, respectively, Ramanadham & Viswanadham (1970), Idso and Jackson (1969) and Bignami et al. (1995) and after parameterization of models: Bárbaro et al. (2010); Aubinet (1994) and Andreas & Ackley (1982).